(untitled) (Journal of Bangladesh Academy of Sciences, 2022)
Considering the importance of the fish and fish products as a vital part of the human diet in Bangladesh, the study aimed to estimate the microbial load, identify the E. coli and observe the isolates antibiogram pattern. Standard plate count technique, as well as the 3-tube most probable number (MPN) method, were applied to estimate the total viable bacteria (TVB) and total coliforms (TC), total fecal coliforms (TFC), and E. coli, respectively. Approximately 61.91% of samples fell into the marginally acceptable limit for TVB count, while 66.67% and 95.25% of examined species exceeded the threshold limit for TC and TFC, respectively (p<0.05). Around 90% of samples were contaminated with E. coli. A culture sensitivity test revealed that cent percent strains harbored resistance to penicillin, rifampicin, and erythromycin. Multiple antibiotic resistance (MAR) index above 0.2 may indicate the misuse or overuse of antibiotics. The findings highlight the potential food safety hazards associated with fish concerning the random use of antibiotics. J. Bangladesh Acad. Sci. 46(1); 9-18: June 2022